Trans-Sectual Identity: Materials for the Study of the Praśnottararatnamālikā, a Hindu/Jaina/Buddhist Catechism (I) - Silk, Jonathan A. (Indo-Iranian journal, 2019)
The Praśnottararatnamālikā is a small tract containing 62 questions, paired with their answers. It is extraordinary that this text has been transmitted within Hindu, Jaina and Buddhist traditions, in Sanskrit, Prakrit and Tibetan, variously attributed to different authors. The present study examines what is known of the text, which from early on drew the attention of modern scholars, and presents editions of its Sanskrit and Tibetan versions, along with a translation and annotations.